The Assessment of Genetic Diversity of Venturia inaequalis Isolates Obtained from Turkey and Europe by Molecular Markers - Suat Kaymak; Nuh Boyraz; Hasan Pınar (Journal of Agricultural Sciences)
Apple scab Venturia inaequalis Cke Wint is the main disease of apple trees not only in the world but also in Turkey. The disease can cause severe yield losses in all Turkish apple orchards. Genetic diversity and relatedness of apple scab Venturia inaequalis Cke Wint isolates collected from Turkey and Europe were investigated in this study through molecular markers. RAPD, ISSR, SSR and SRAP markers were used in the molecular studies. Results obtained by marker system revealed that isolates were quite separated from each other and it is appeared to exist a variation between them. Genetic relatedness between the isolates are very close to each other, and difference among the groups is not significant due to host specificity and geographical location. The groups are consisted of more number of isolates when SSR and SRAP markers are used compared with ISSR and RAPD markers. Using SSR and SRAP markers are preferable to provide more informative outcomes because of ease of use, repeatability and specificity